SPECIFIC CHARACTERISTICS OF ECOLOGICAL EDUCATION THROUGH ENVIRONMENT PROTECTION IN PRIMARY CLASS STUDENTS - Tangirkulov Elmurod Aliyarovich (Scholar Express Journal, 2023)
This article talks about the specific features of improving the mechanisms of environmental education by protecting the environment and the activities carried out to improve the mechanisms of environmental education by protecting the environment among elementary school students
Keywords: class; students; environment